2016
DOI: 10.1007/s00167-016-4198-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of arthroscopy-guided suprascapular nerve block combined with ultrasound-guided interscalene brachial plexus block for arthroscopic rotator cuff repair: a randomized controlled trial

Abstract: Randomized controlled trial, Level I. ClinicalTrials.gov Identifier: NCT02424630.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(41 citation statements)
references
References 29 publications
0
40
0
1
Order By: Relevance
“…Additionally, in the ISBPB + SSNB group, six patients experienced “double rebound” phenomenon, in which they had two distinct periods of hyperalgesia corresponding to the expected termination of effect of each individual block. There was however a statistically significant delay in onset ( p < 0.001) and a significantly reduced severity (p = 0.001) of rebound pain in the ISBPB + SSNB group compared with ISBPB alone [69]. The duration of ISBPB and SSNB has been reported as 8 h and up to 24 h respectively [62,70].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, in the ISBPB + SSNB group, six patients experienced “double rebound” phenomenon, in which they had two distinct periods of hyperalgesia corresponding to the expected termination of effect of each individual block. There was however a statistically significant delay in onset ( p < 0.001) and a significantly reduced severity (p = 0.001) of rebound pain in the ISBPB + SSNB group compared with ISBPB alone [69]. The duration of ISBPB and SSNB has been reported as 8 h and up to 24 h respectively [62,70].…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al. added a suprascapular nerve block to an interscalene block in a placebo‐controlled study and identified lower pain scores for the group that received the suprascapular nerve block at 3 h, 6 h, 12 h, 18 h and 24 h after surgery. Opioid consumption was not reported.…”
Section: Resultsmentioning
confidence: 99%
“…11 Moreover, long-lasting effect has been reported when both periarticular injection and ISB were performed concomitantly. 12 We hope that this paper will lead to an active discussion on postoperative pain management after arthroscopic rotator cuff surgery. And before undergoing arthroscopic rotator cuff surgery myself, I cannot help but hope for the development of postoperative pain management.…”
Section: See Related Article On Page 1243mentioning
confidence: 95%